An analysis of Land Mark impact factors on high‐rise residential buildings value assessment - Moon, Sung-Kon; Lee, Sang-Hyo; Min, Kyung-Min; Lee, Joo-Sung; Kim, Ju-Hyung; Kim, Jae-Jun (International Journal of Strategic Property Management, 2010)
Due to the improvement of high technology and the excessive congestion of cities, the number of high rise buildings has been increasing gradually. Also the number of studies about this issue has been rising relatively. However the previous research on super high rise buildings focused mostly on the use of public space from building plan perspective, survey ‘of residents’ satisfaction evaluation, construction technology and structural technology. Little research is done on the economic analysis of landmark factors. The purpose of this study is to find landmark factors that can be quantitatively measured, collect data on super high rise residential buildings in Seoul. Find the intrinsic values of the landmarks, and analyze how these values differ in areas with different densities, i.e. in Gangnam‐area and Yeongdeungpo‐gu and in other areas. It is expected that the results of this study can be used to set an appropriate price of super high rise building in consideration of its landmark value in different area.First Published Online: 18 Oct 2010